Principals’ Quality Control Measures and Secondary School Goal Attainment in Obudu Local Government Area, Cross River State-Nigeria - Clement, Eton Idorenyin; Ngieagba, Kajang Margaret; Omorobi, Omorobi Garieth (International Journal of English Literature and Social Sciences (IJELS), 2020)
This study investigated quality control measures adopted by school principals to enhance attainment of secondary education goals in Obudu Local Government Area in Cross River State. Specifically, the study assessed the relationship between quality control measures of effective instructional supervision, teacher performance evaluation and secondary school goal attainment. To achieve the purpose of the study, two hypotheses were formulated to guide the study. Survey research design was adopted for the study, all the 26 principals of public secondary schools in Obudu LGA were both the population and sample for the study using the census approach. An instrument tittled: Principals’ Quality Control Measures and Secondary School Goal Attainment Questionnaire (PQCMSSGAQ) was used for data collection. The instrument was validated by five experts in Educational Management and Educational Measurement and Evaluation in University of Calabar. The instrument obtained a reliability coefficients ranging from .75-.81 using the split half method. Data was collected and analyzed through Pearson product moment correlation analysis, the results of the study revealed that there is a significant relationship between effective instructional supervision, teacher performance evaluation and secondary school goal attainment. It was therefore recommended that principals should constantly carry out routine and periodic instructional supervision and teacher performance evaluation to fast track secondary school goal attainment.